Three new Diplozoidae mitogenomes expose unusual compositional biases within the Monogenea class: implications for phylogenetic studies - Dong Zhang; Hong Zou; Shan G. Wu; Ming Li; Ivan Jakovlić; Jin Zhang; Rong Chen; Wen X. Li; Gui T. Wang (BMC Evolutionary Biology, 2018)
Abstract Background As the topologies produced by previous molecular and morphological studies were contradictory and unstable (polytomy), evolutionary relationships within the Diplozoidae family and the Monogenea class (controversial relationships among the Discocotylinea, Microcotylinea and Gastrocotylinea suborders) remain unresolved. Complete mitogenomes carry a relatively large amount of information, sufficient to provide a much higher phylogenetic resolution than traditionally used morphological traits and/or single molecular markers. However, their implementation is hampered by the scarcity of available monogenean mitogenomes. Therefore, we sequenced and characterized mitogenomes belonging to three Diplozoidae family species, and conducted comparative genomic and phylogenomic analyses for the entire Monogenea class. Results Taxonomic identification was inconclusive, so two of the species were identified merely to the genus level. The complete mitogenomes of Sindiplozoon sp. and Eudiplozoon sp. are 14,334 bp and 15,239 bp in size, respectively. Paradiplozoon opsariichthydis (15,385 bp) is incomplete: an approximately 2000 bp-long gap within a non-coding region could not be sequenced. Each genome contains the standard 36 genes (atp8 is missing). G + T content and the degree of GC- and AT-skews of these three mitogenome (and their individual elements) were higher than in other monogeneans. nad2, atp6 and nad6 were the most variable PCGs, whereas cox1, nad1 and cytb were the most conserved. Mitochondrial phylogenomics analysis, conducted using concatenated amino acid sequences of all PCGs, indicates that evolutionary relationships of the three genera are: (Eudiplozoon, (Paradiplozoon, Sindiplozoon)); and of the three suborders: (Discocotylinea, (Microcotylinea, Gastrocotylinea)). These intergeneric relationships were also supported by the skewness and principal component analyses. Conclusions Our results show that nad2, atp6 and nad6 (fast-evolving) would be better candidates than cox1 (slow-evolving) for species identification and population genetics studies in Diplozoidae. Nucleotide bias and codon and amino acid usage patterns of the three diplozoid mitogenomes are more similar to cestodes and trematodes than to other monogenean flatworms. This unusual mutational bias was reflected in disproportionately long branches in the phylogram. Our study offsets the scarcity of molecular data for the subclass Polyopisthocotylea to some extent, and might provide important new insights into the evolutionary history of the three genera and three suborders.